The lexicon used in ironic conversations - Ramos Quispe, Teresa (2012)
This article analyses and explains in a qualitative way verbal irony in real conversations noting how they develop when a special context is taken into consideration. As well as this a difference is distinguished between humorous and critical, because irony is not only used to criticise and annoy, but also to establish a link of complicity among the speakers. The examination of the vocabulary used has been the key note of this investigation because in the conversations literary figures have been found charged with critical irony and that have been used as attenuators to relieve the responsabilities of the speaker. As well as this the hearer will have had to interpret the declarations correctly to discern the pertinent meaning.